Pengaruh Kualitas Pelayanan dan Nilai Konsumen terhadap Loyalitas Pelanggan pada Jasa Pencucian Pakaian Laundry Syariah di MJ Laundry Cikarang - Yeni Masruri (Jurnal Al-fatih Global Mulia, 2025)
The laundry business is a business engaged in the service sector. Human needs for the existence of laundry. Laundry business is a business that follows the changing lifestyle. This study aims to analyze and partially determine the effect of Service Quality on Customer Loyalty and Consumer Value. Customers and Consumer Value have an effect on Customer Loyalty and analyze and know simultaneously Service Quality and Consumer Value have an effect on Customer Loyalty at Sharia Laundry. Analysis using multiple linear regression tests and hypothesis testing using the t-test and f-test with hypothesis testing using the t-test and f-test with the help of the spss version 2.0 program. Based on hypothesis testing it can be concluded that Service Quality Service has t-count>t-table, namely 1.851> 1.701 with a significance level of 0.001 <0.05. significance level 0.001 <0.05. Likewise with Consumer Value, Consumer Value has t-count> t-table namely 2.557> 1.701 with a significance value of 0.002 <0.05. significance of 0.002 <0.05 means that each variable partially has a significant effect on Customer Loyalty.  Likewise with the results of the f test state that in multiple linear regression testing shows the results of f count> f table, namely 5.697> 3.354 with a significance level of 0.000 <0.05, meaning that each variable partially has a significant effect on Customer Loyalty. significance level of 0.000 <0.05, so it is proven that the two variables of Service Quality and Consumer Value simultaneously have a significant effect on Customer Loyalty.